Software piracy in United States, Australia, Taiwan, Hong Kong and Singapore. - Ling, Kia Mien. (2008)
In this project, we looked into software piracy in United States, Australia,Taiwan,Hong Kong and Singapore. We also study the individualism-collectivism, power distance and long-term orientation dimensions of the five countries, and seek to find a linkage between software piracy and these three dimesions we studied.